Potensi Pemanfaatan Limbah Pasar Kubis-Kubisan (Brassica Oleracea L), Pisang (Musa Paradisiaca), Dan Umbi Akar (Tuber Rhizogenum) Sebagai Bahan Baku Energi Terbarukan Biogas - Nuraliyah, Andi; Raking, Jumrin; Marzuki, Ismail (Jurnal Jaring SainTek, 2023)
One form of energy that can overcome reduced energy sources is biogas obtained through the cooking process using market waste such as cabbage, bananas and root tubers with EM4 bioactivator. This study aims to determine the C/N ratio, the volume of methane gas, and the chemical composition of the gas as measured by the ECOM J2KN gas analyzer and the FTIR Spectro. Based on the results of the study, the optimum C/N ratio for the quickest time of 7 days for raw materials for cabbage, bananas, root tubers were 14.5; 10.6 and 23.9. The volume of methane (ml) obtained were 151 ml, 186 ml, and 289 ml. The mixture of the three raw materials with and without the EM4 bioactivator obtained methane gas volumes of 171 and 143. The main chemical composition of biogas detected on the J2KN ECOM tool was Methane (CH4) 55.81%. Carbon Dioxide (CO2) 14.46%, and Oxygen (O2) 17.73%. The chemical gas composition with the CH group function was obtained at a wavelength of 2933.73 cm-1. These results indicate that vegetable waste from cabbage, bananas, and root tubers can be used as raw material for biogas.